EVALUATION OF INTERBODY FUSION TWO YEARS AFTER LLIF PROCEDURE - ROSA,FÁBIO (2020)
ABSTRACT Objectives The LLIF technique, extreme lateral interbody fusion, reaches the disc laterally through the psoas muscle, offering adequate access to the disc space with the added benefit of preventing iatrogenic injury to abdominal vascular structures (aorta and vena cava), the sympathetic plexus (reduces incidence of retrograde ejaculation) and neural structures, that is, preservation of the spinal nerves that cross the posterior aspect of the muscle. The objective of this study is to verify the rates of interbody fusion with the LLIF technique. Methods Retrospective, single center, comparative, non-randomized study. The presence of bone mass with increased hypotransparency in the areas of fusion will be analyzed. For the evaluation of the fusion, the Classification of interbody fusion success: Brantigan, Steffee, Fraser (BSF) will be used. Results Fifty-nine (86%) patients presented complete fusion of the approached level (BSF-3) six months after the procedure. One year after the procedure, 87% of the patients had complete fusion. Similar results were confirmed at two years. Conclusions We conclude that the technique of lateral interbody arthrodesis is safe and effective for the treatment of low back pain, with a fusion rate of 90% in two years. Level of Evidence III. Retrospective study, single center, non-randomized.